Evaluation of Antibiotic Biodegradation by a Versatile and Highly Active Recombinant Laccase from the Thermoalkaliphilic Bacterium Bacillus Sp. Fnt - Cortés-Antiquera, R; Blamey-Alegria, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Laccases are industrially relevant enzymes that have gained great biotechnological importance. To date, most are of fungal and mesophilic origin; however, enzymes from extremophiles possess an even greater potential to withstand industrial conditions. In this study, we evaluate the potential of a recombinant spore-coat laccase from the thermoalkaliphilic bacterium Bacillus sp. FNT (FNTL) to biodegrade antibiotics from the tetracycline, β-lactams, and fluoroquinolone families. This extremozyme was previously characterized as being thermostable and highly active in a wide range of temperatures (20–90 °C) and very versatile towards several structurally different substrates, including recalcitrant environmental pollutants such as PAHs and synthetic dyes. First, molecular docking analyses were employed for initial ligand affinity screening in the modeled active site of FNTL. Then, the in silico findings were experimentally tested with four highly consumed antibiotics, representatives of each family: tetracycline, oxytetracycline, amoxicillin, and ciprofloxacin. HPLC results indicate that FNTL with help of the natural redox mediator acetosyringone, can efficiently biodegrade 91, 90, and 82% of tetracycline (0.5 mg mL−1) in 24 h at 40, 30, and 20 °C, respectively, with no apparent ecotoxicity of the products on E. coli and B. subtilis. These results complement our previous studies, highlighting the potential of this extremozyme for application in wastewater bioremediation. © 2024 by the authors.